Math, asked by venombmgo, 1 month ago

prove that:
tan² x sec² y- sec² x tan² y = tan² x- tan² y​

Answers

Answered by ayandeepdas123456
0

Answer:

1 is right answer

(secx . secy + tanx . tany)² – (sec x . tan y + tan x . sec y)²

= sec² x . sec² y + tan² x . tan²y + 2 sec x . sec y . tan x . tan y – sec² x . tan² y – tan² x . sec²y – 2 sec x . sec y . tan x . tan y

= sec² x . sec²y + tan²x . tan² y – sec² x . tan²y – tan² x . sec²y

= sec²x . sec²y – sec²x . tan²y – tan²x . sec²y + tan² x . tan²y

= sec²x (sec²y – tan²y) – tan²x (sec²y – tan²y)

= sec²x – tan²x = 1

Similar questions